Estimation of Construction Duration for Roads and Bridges in Nepal - Pokhrel, Prakriti; Misra, Jibendra; Nepal, Dikshit Babu; Adhikari, Pradip (Nepal Journal of Civil Engineering, 2021)
Precise estimation of contract duration is a tough job in the construction field given the uncertainties involved in it. The construction industry for Roads and Bridges in Nepal is in a transitional phase and the working procedures varies on the individual capacity of each contractor. So, a practical approach is necessary for developing a methodology for estimation of duration. At present the estimated contract duration lacks uniformity among the projects of similar size and nature. With time extension issue getting much attention in recent amendments of PPR, estimation of duration has yet in the shadows among the lawmakers. This research aims at developing an empirical formulae for determination of contract duration based on the historical data of roads and bridges completed within the last five years. A total of 83 bridges and 78 road projects were analyzed. Regression analysis was carried out for developing a mathematical relation between time and cost of the project. The data was made to fit in Browmillow’s time-cost model. Apart from the cost of the project, there are other factors that affect the duration of the project. To address these project specific requirements, modification were recommended to the time-cost model by introducing coefficients in the empirical relation. As per the obtained equation, contract duration is directly proportional to the cost. However, the rate of increase in contract duration decreases with increase in cost. The reason for this is due to the higher level of parallel activities and better use of technologies for the contracts with higher cost. This model can be useful for government agencies, contractors and consultants involved in construction and procurement of roads and bridges in Nepal. The empirical formula obtained as an outcome of this research is applicable for roads and bridge projects of Nepal with estimated amount greater than two crore.